Application and Possible Mechanism of Microbial Fermentation and Enzyme Catalysis in Regulation of Food Flavour - Feng Wang; Mingtong Wang; Ling Xu; Jingya Qian; Baoguo Xu; Xianli Gao; Zhongyang Ding; Kai Cui (Foods)
Flavor compounds are key determinants of food sensory quality, originating from natural sources, processing, or artificial additives. Although physical and chemical methods can effectively enhance food flavor, microbial fermentation and enzyme catalysis technology possess good potential in food flavor regulation due to their mild reaction conditions and high safety. In addition, the high efficiency and specificity of enzymes help to shorten the production cycle and accurately regulate food flavor. This review focuses on the application and regulation mechanism of bacteria, yeast, other fungi, and mixed microbe fermentation systems in flavor production. The utilization and catalytic reaction schemes of oxidoreductases, transferases, and hydrolases in flavor regulation are also deeply explored, and suggestions for the application of microbial fermentation and enzyme catalysis technology in flavor regulation are discussed.